2015
DOI: 10.1021/acs.chemmater.5b01350
|View full text |Cite
|
Sign up to set email alerts
|

Series of Quinoidal Methyl-Dioxocyano-Pyridine Based π-Extended Narrow-Bandgap Oligomers for Solution-Processed Small-Molecule Organic Solar Cells

Abstract: Small molecules with narrow bandgap of <1.6 eV can harvest the visible and near infrared solar photons. In this paper, we report a new method to achieve narrow bandgap small molecule donors by using electron-deficient quinoidal methyldioxocyano-pyridine (MDP) to induce possible quinoidal resonance structure along the conjugated A−π−D−π−A backbone. Practically, two MDP moieties are covalently linked onto an electron-rich benzodithiophene (BDT) through the oligothiophene (0T−5T) π-bridge. The affording small mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 61 publications
0
30
0
Order By: Relevance
“…Detailed synthesis procedures are provided in Scheme and supporting information. Briefly, compounds 1 and 2 were prepared according to the reported procedure and then coupled together to form the p‐type block (benzodithiophene‐rhodanine, BDTRh) via the Knoevenagel condensation . BDTRh–[6,6]‐phenyl‐C 61 butyric acid methyl ester (PCBM) was synthesized in 42% yield by connecting BDTRh with two PCBM wings via an esterification reaction .…”
Section: Resultsmentioning
confidence: 99%
“…Detailed synthesis procedures are provided in Scheme and supporting information. Briefly, compounds 1 and 2 were prepared according to the reported procedure and then coupled together to form the p‐type block (benzodithiophene‐rhodanine, BDTRh) via the Knoevenagel condensation . BDTRh–[6,6]‐phenyl‐C 61 butyric acid methyl ester (PCBM) was synthesized in 42% yield by connecting BDTRh with two PCBM wings via an esterification reaction .…”
Section: Resultsmentioning
confidence: 99%
“…23,24 They can efficiently tune the FMOs energy levels through an intramolecular charge transfer, which leads to a narrow band gap, intense light absorption, and high PCEs. [25][26][27] Additionally, the intermolecular stacking, lm morphology, and charge transport properties can be determined by the type and length of side chains of D-A molecular structures. 28,29 It has been reported that a…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, oligothiophenes, including monotiophene [16,20], bithiophene [16], terthiophene [8,1415 1719 2123 26], quaterthiophene and quinquethiophene [27], and cyclopentadithiophene [28] have been utilized as the π-bridge in constructing conjugated molecules with a BDT core. Among these 3,3''-dihexyl-2,2':5':2''-terthiophene (3T) is the most widely used π-bridge.…”
Section: Introductionmentioning
confidence: 99%
“…In order to minimize the synthesis efforts, structurally symmetric oligothiophene units are mostly used for constructing A–π–D–π–A-type molecules with a BDT core. Interestingly, although various terthiophene-based derivatives with a BDT core have been reported, there is only one paper that reported the synthesis and characterization of BDT derivatives based on oligothiophene π-bridges with more than three thiophene units [27], where symmetric quater- and quinquethiophenes were used as the π-conjugation bridge. Surprisingly, the quaterthiophene-bridged compound showed the worst photovoltaic performance when blending with a fullerene derivative as the photoactive layer.…”
Section: Introductionmentioning
confidence: 99%